AQbD based green UPLC method to determine mycophenolate mofetil impurities and Identification of degradation products by QToF LCMS - Siva Krishna Muchakayala; Naresh Kumar Katari; Kalyan Kumar Saripella; Henele Schaaf; Vishnu Murthy Marisetti; Leela Prasad Kowtharapu; Sreekantha Babu Jonnalagadda (Scientific Reports, 2022)
Abstract We report an ideal method for quantifying impurities in mycophenolate mofetil drug substances and their oral suspension preparations. We developed a systematic and eco-friendly analytical approach utilizing quality by design (QbD) and green chemistry principles. Initially, the critical method parameters (CMPs) were screened using a D-optimal design. The robust final method conditions were optimized using a systematic central composite design (CCD). Through graphical and numerical optimization, the protocol conditions were augmented. The pH of mobile phase buffer (25 mM KH2PO4) (MP-A), initial gradient composition (% MP-A), flow rate (mL min−1), and column oven temperatures (°C) are 4.05, 87, 0.4, and 30, respectively. The best possible separation between the critical pairs was achieved while using the Waters Acquity UPLC BEH C18 (100 × 2.1) mm, 1.7 µm analytical column. A mixture of water and acetonitrile in the ratio of 30:70 (v/v) was used as mobile phase-B for the gradient elution. The analytical method was validated in agreement with ICH and USP guidelines. The specificity results revealed that no peaks interfered with the impurities and MPM. The mean recovery of the impurities ranged between 96.2 and 102.7%, and the linearity results r > 0.999 across the range of LOQ – 150%. The precision results (%RSD) ranged between 0.8 and 4.5%. The degradation products formed during the base-induced degradation were identified as isomers of mycophenolic acid and sorbitol esters using Q-ToF LC–MS and their molecular and fragment ion peaks. The developed method eco-friendliness and greenness were assessed using analytical greenness (AGREE), green analytical procedure index (GAPI), and analytical eco score, and found it is green.